N-3 Polyunsaturated Fatty Acids Stimulate Bile Acid Detoxification in Human Cell Models - Anna Cieślak; Jocelyn Trottier; Mélanie Verreault; Piotr Milkiewicz; Marie-Claude Vohl; Olivier Barbier (Canadian Journal of Gastroenterology and Hepatology)
Cholestasis is characterized by the accumulation of toxic bile acids (BAs) in liver cells. The present study aimed to evaluate the effects of n-3 polyunsaturated fatty acids (n-3 PUFAs), such as docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids, on BA homeostasis and toxicity in human cell models. The effects of EPA and/or DHA on the expression of genes involved in the maintenance of BA homeostasis were analyzed in human hepatoma (HepG2) and colon carcinoma (Caco-2) cells, as well as in primary culture of human intestinal (InEpC) and renal (RPTEC) cells. Extracellular BA species were quantified in culture media using LC-MS/MS. BA-induced toxicity was evaluated using caspase-3 and flow cytometry assays. Gene expression analyses of HepG2 cells reveal that n-3 PUFAs reduce the expression of genes involved in BA synthesis (CYP7A1, CYP27A1) and uptake (NTCP), while activating genes encoding metabolic enzymes (SULT2A1) and excretion transporters (MRP2, MRP3). N-3 PUFAs also generate a less toxic BA pool and prevent the BA-dependent activation of apoptosis in HepG2 cells. Conclusion. The present study reveals that n-3 PUFAs stimulate BA detoxification.